COVID-19 rapid evidence profile #46: How were downstream health-promotion approaches that focus on individual behaviour change used during the public-health response to the COVID-19 pandemic? - Waddell, K; Velez, CM; DeMaio, P; Bain, T; Alam, S; Wilson, MG (My University, 2023)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about downstream health-promotion approaches that focus on individual behaviour change used during the public-health response to the COVID-19 pandemic in response to a decision-maker’s request.
Keywords: health; promotion; behaviour; public; COVID-19